A crise econômica atual: um ensaio de interpretação marxista - Ribeiro, Nelson (2022)
The 70s are marked by the birth of a threefold crisis: an economic one, a crisis in economic policy and a crisis in the economic theory which had, until then, esmonic. The sharp growth in the world capitalist economy, the considerable decrease in the range of cyclic movements, during the post-war period, seem to have validated the Keynesian concepts arrived in power following the 1929 crisis and the subsequent second World War. In 1974-75 everything changed. The crisis reappeared in all its depth, along with it there set in a feeling of scepticism regarding the efficacity of state intervention. At the same time with all their migth there reemerged the "liberal" and monetarist thesis which had been dethroned by the impact of the events of the 30s and Keynes criticism. The purpose of this paper is to fit into the framework of the debate that exists today regarding the crisis and state intervention and to propose an interpretation of the economic difficulties triggered off by the 1974-75 crisis, from the theoretical elements left by Marx.